Inconsistencies in How Environmental Risk Is Evaluated in Sweden for Dumping Dredged Sediment at Sea - Bruce, Peter; Bradshaw, Clare; Ohlsson, Yvonne; Sobek, Anna; Christiernsson, Anna (Frontiers in Marine Science, 2021)
Millions of tons of dredged sediment are dumped at sea annually. International conventions limit dumping when there is a risk of adverse ecological effects, for example if the sediment is contaminated. However, the perception of risk differs substantially among stakeholders and in Sweden there is a lack of guidelines for how to address such risk. In the current study, we examined exemptions to the Swedish ban on dumping at sea, to explore the extent of dumping and how ecological aspects were considered in the evaluation of risks. We analyzed data from all cases granted exemption by county administrative boards and all court cases considering exemption to the ban from the beginning of 2015 to June 2020. We found that while dumping is the least common alternative management method for dredged sediment in total number of cases (98/792), dumping is the main method in terms of volume (30.8 /38.2 million m3). When considering exemptions, the courts mainly evaluated the risk for exposure to contaminants and resuspended sediment to the environment adjacent to the dumpsite. The risks from contaminants were characterized based on various lines of reasoning, mainly relying on reference values not based on a scientific correlation to environmental risk. We argue that the evaluations were not in line with current regulations and international conventions as they insufficiently accounted for the ecotoxicological risk of the dumped sediment. These issues are potentially similar in other Baltic Sea countries, where there is a similar dependency on binary chemical limit values.